Magnetic hyperthermia induces effective and genuine immunogenic tumor cell death with respect to exogenous heating. Issue 28 (1st July 2022) - Yan, Bin; Liu, Chen; Wang, Siyao; Li, Hugang; Jiao, Ju; Lee, Wee Siang Vincent; Zhang, Song; Hou, Yayi; Hou, Yuzhu; Ma, Xiaowei; Fan, Haiming; Lv, Yi; et al.
Abstract : This study systematically verified that magnetic hyperthermia (MH) with intracellular heating can induce genuine immunogenic tumor cell death for effective antitumor therapy, while exogenous heating fails to elicit this effect. Abstract : Immunogenic cell death (ICD) can improve the therapeutic effects of cancer immunotherapy by initiating adaptive immune responses. Unlike the exogenous hyperthermia modality in clinics, magnetic hyperthermia (MH) is characterized by an iron oxide nano-agent acting as a heating source and the effects induced by heating acting at the intracellular region. However, the immunological effects of endogenous heating generated during MH and exogenous heating, and the difference in damage-associated molecular pattern (DAMP) emissions correlating with the ICD are unclear; whether MH elicits genuine ICD remains unknown. Herein, we have identified 10 distinct DAMP correlates of ICD induced by intracellular MH, and found that only heat shock proteins 70/90 were expressed after water bath heating (exogenous hyperthermia) in human triple-negative breast cancer (TNBC) MDA-MB-231 cells, murine TNBC 4T1 cells, and surgically resected specimens of ductal breast cancer from patients. In vivo vaccination assays were performed in immunocompetent BALB/c mice. The results demonstrated that MH with endogenous heating could stimulate the genuine ICD on 4T1 cells and achieved optimal therapeutic effects on 4T1 tumors, whereas exogenous heating under the same conditions failed to elicit these effects. These findings with regard to the MH induced genuine ICD with high efficiency are critical for the development of safe and effective therapeutics to amplify the therapeutic responses of cancer immunotherapy.